SAVI Learning Model is a Solution for Teachers in Active Learning - Destiani Rahmawati; Mohamad Maulidin Alif Utama; Ike Hilatun Nisa (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
The learning process in each primary and secondary education unit must be interactive, inspiring, fun, challenging, and motivating students to participate actively and provide sufficient space for initiative, creativity and independence in accordance with the talents, interests, and physical and psychological development of the subject learners or perpetrators of learning activities. In order for students to act as learning actors, the teacher should plan learning activities that require students to do a lot of learning activities. SAVI is a solution in learning problems for teachers. The purpose of this research is to describe SAVI learning model. The method used is literature study. Results of this research showed that the SAVI learning model able to change and transform the learning paradigm from teacher centered to student centered so that the learning is more competitive and fun.